MATCHING COMMUNICATION WITH CHATGPT: AN INNOVATIVE SOLUTION TO MAINTAIN HARMONIOUS RELATIONSHIPS BETWEEN CLOSE FRIENDS - Joy Lasmita Siregar; Sophia Tithania Sitorus; Rita Hartati (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
This study examined the role of ChatGPT, an AI-powered language model, in supporting harmonious communication among close friends through the application of Matching Communication techniques derived from Neuro-Linguistic Programming (NLP). A quantitative method was used to collect data from 25 university students who actively used ChatGPT in their digital communication. The research focused on key aspects such as message clarity, emotional expression, tone adjustment, and conflict resolution. Results showed that ChatGPT enabled users to articulate their messages more clearly, adjust their language to match their conversational partner’s style, and manage conflicts more effectively. Most participants agreed that aligning communication styles increased comfort in conversations and helped reduce misunderstandings. However, while ChatGPT was perceived as a valuable aid, it was not considered a replacement for face-to-face communication, which remains essential for emotional depth and relational authenticity. This study concluded that ChatGPT, when used with awareness and intention, can enhance interpersonal communication by supporting empathy and clarity, but must be complemented by real human interaction to sustain meaningful relationships.